Penggunaan Zoe pada Pulpitis Reversible Anak - Mutiara Aurellia Widyarini; Nendika Dyah Ayu Murika Sari (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Background: Zinc Oxide Eugenol (ZOE) is the most widely used root canal filling material in primary teeth. Its sedative effect on the pulp and its ability to effectively seal the root canal contribute to the success of pulpectomy procedures. One of the main advantages of ZOE is its slow resorption rate, which allows it to maintain its integrity over time while the primary tooth remains functional. Purpose: ZOE is used to treat reversible pulpitis. Case: An 8-year-old boy came to Soelastri Dental and Oral Hospital complaining of a cavity in his lower left molar that was sensitive to cold. Case Management: The results of clinical and radiographic examinations indicated that the treatment performed in this case was a pulpotomy using ZOE material and a final restoration with SSC. Conclusion: The pulpotomy treatment was evaluated successfully, and the tooth was restored with a stainless steel crown.